Maps and Map Skill Progression in Primary Geography in International Comparison - Bagoly-Simó, Péter; Binimelis, Jaume (Journal of Geography Education, 2022)
This paper explores how primary textbooks introduce maps and progressive map skill acquisition and development. Against the background of the Map Skills Model (Hemmer et al. 2010), this study applied a mixed-methods approach to a sample consisting of twelve Catalan (Ciènces Socials) and four German (Sachunterricht) textbooks. The results uncovered an overall erosion of cartographic content and a varying diversity of map types included in the textbooks. Tasks fostering map skill acquisition lack a clear concept of progression and mainly focus on map decoding and production, with interpretation and evaluation missing from all textbooks. The case studies also showed differences in the chronology, typology, and hierarchy of maps and map-related tasks.
Keywords: map skills, Geography, primary education, textbook